Optimalisasi Peran Kepala Desa dalam Mengawasi Penggunaan Dana Desa untuk Mencegah Korupsi - Hasibuan, Tornado; Panjaitan, Budi Sastra (FISIP Universitas Malikussaleh, 2025)
The authority given to the village government to manage village funds brings many benefits, especially in village development. Supervision of village funds is also very necessary to prevent criminal acts of corruption. The research method used in this research is descriptive analytical which describes in detail the social phenomena at the heart of the problem using empirical research and using qualitative data analysis. The results of the research show that village heads prevent criminal acts of corruption by recognizing the modus operandi of corruption in village funds, improving the quality of village officials, monitoring the management of village funds and strengthening cooperation with village assistants. Obstacles encountered and solutions implemented in preventing criminal acts of corruption in village funds are the low quality of human resources in managing village funds with the solution of providing technical guidance, low integrity of village officials in managing village funds with the solution of providing integrity culture outreach and low community participation in supervision. managing village funds with the solution of providing information to the community by socializing the use of village funds. The criminal act of corruption in village funds is any action that is detrimental to the state and villages, destroying the economic system, democratic system, political system, legal system, government system and social order. Efforts to prevent criminal acts of corruption in village funds can be carried out by monitoring the use of village funds.